The Effects of Random and Blocked Practice with an Emphasis on the Changes in GMP and Parameter on Acquisition, Retention and Transfer of Table Tennis - Alireza Farsi; Behrooz Abdoli; Mohammadreza Gasemian (University of Tehran, 2013)
The aim of this study was to compare the effects of random and blocked practices with respect to the changes in generalized motor program (GMP) and parameter on acquisition, retention and transfer of table tennis service. For this purpose, 32 subjects were randomly assigned to four groups (8 subjects each group). In the first two groups, GMP changed with blocked and random arrangements while in the last two groups, parameter changed with those arrangements. After pretest, participants completed 300 trials in each task (totally 900 trials) and then they participated in posttest, retention and two transfer tests with different aims. The data were analyzed by two-way ANOVA and ANOVA with repeated measures (P˂0.05) and Bonferroni post hoc test was used to mark the differences of the groups. The findings showed that despite the type of changes, the random practice caused better performance than blocked practice and these advantages of random practice in GMP changes were greater.  However, these effects not only were observed in the same situation but also were maintained in other contexts. In addition, these effects not only influenced performance but also caused the participants to perform the tasks with more efficiency, more cognitive effort and less attention.